Pengaruh disiplin kerja dan lingkungan kerja terhadap kinerja guru di SMA Negeri 6 Kabupaten Tangerang - Zahrawaani Kurdi, Annisa; Setiawan, Aries; Saparudin, Dede (Universitas Tangerang Raya, 2024)
: Overall, education is a long-term investment that can bring great benefits to individuals and countries. The aim of this research is to find out whether there is an influence of Work Discipline and Work Environment on Teacher Performance at Sma Negeri 6 Tangerang Regency. This research method uses quantitative methods. The sampling method uses non-probability sampling or saturated sampling. The number of samples in this research was 65 respondents. Data collection techniques use questionnaires, interviews, observation and literature study. Then the test tool used is SPSS software. The research results show that there is a partial influence of Work Discipline and Work Environment on Teacher Performance. Work Discipline with a value of 5,625 then Work Environment with a value of 3,890 which is greater than the T table with a value of 1.998 and a sign value smaller than 0.05. So it can be concluded that the Work Discipline variable and the Work Environment variable influence the Teacher Performance variable. Simultaneous research results with a calculated F value of 107,595 are greater than the F table of 3.22, so the Work Discipline and Work Environment variables have a joint effect on the Teacher Performance variable. 77.6% is influenced by Work Discipline and Work Environment, 22.4% is due to other factors. It can be concluded based on the research results that Work Discipline and Work Environment on Teacher Performance have a positive and significant relationship